Genetics and clinical characteristics of keratoconus - Štabuc-Šilih, Mirna (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 2010)
Keratoconus (KC) is a bilateral, non-inflammatory, and progredient corneal ectasia that mostly occurs as a sporadic disorder, but it has long been recognized that a significant minority of patients also exhibit a family history. In recent years several candidate genes such as VSX1 and SOD1 have been proposed, and some disease-causing mutations have been identified. Latelyresearch has also focused on collagen genes, especially those that are differentially expressed in KC cornea. Alterations in COL4A3 and COL4A4 genes may be responsible for decreases in collagen types I and III, a feature often detected in KC. To investigate the role of all four genes in 113 Slovenian patients with sporadic or familial keratoconus, DNA extraction, polymerase chain reaction amplification, and sequencing of both genes were performed. No disease-causing mutations were found, but two previously identified single nucleotide polymorphisms were identified (A128A and 627+23G>A) in the VSX1 gene. D326Y in COL4A3 and M1237V and F1644F in COL4A4 were also found to be significantly associated with KC patients. The absence of pathogenic mutationsin VSX1, SOD1, COL4A3, and COL4A4 genes in our large number of unrelated keratoconus patients indicates that other genetic factors are involved in the development of this disorder; nevertheless, a significant correlation of a few polymorphisms indicates that there could be a link between specific polymorphisms and KC disease.
Keywords: Collagen; Diagnosis; Genetics; genetika; Keratoconus; keratokonus; Keratokunus; Kolagen; Mutacija; mutacije; Mutation; očesne bolezni; polimorfizem; Polimorfizem (genetika); Polymorphism (Genetics); Sequence Analysis, Dna; Zaporedje, analiza, DNA